The Standing of the Regional People's Representative Council Secretariat in Indonesia - Febrian Febrian (Sriwijaya Law Review, 2022)
Indonesia's constitutional system has a clear separation between the judiciary, the legislature and the executive. Likewise, its functions have clear boundaries regulated in the legislation. However, in practice, there is an institution that has two institutional responsibilities simultaneously, namely the Regional People's Representative Council (DPRD) secretariat. Legally, the DPRD secretariat led by the DPRD secretary has responsibilities to the executive, in this case, the governor or regent on the one hand and the DPRD leadership as a legislative body on the other. This generally occurs in Indonesia, where the DPRD secretariat institutional system is regulated through regulations issued by the executive. This study uses a statute approach with a normative juridical method that examines legal products related to the secretariat of the DPRD in Indonesia. As a result, it is believed that the DPRD secretariat institutional system, which is regulated through executive products, violates the higher regulation. Therefore, a fundamental change to the executive legal product is crucial to maintaining the DPRD secretariat's impartiality in carrying out its duties and authorities.